DesignChain: A Smart Contract-based Customized Production Model - Baygin, Nursena; Baygin, Mehmet; Karakose, Mehmet (Ieee, 2020)
Today, thanks to the developing technology, mass production technology is progressing very fast. With these systems, which aim to meet the increasing customer demands correctly, effectively and efficiently, it is aimed to produce customer-specific products. In this method called mass customization, customers can customize the product they demand and create it according to their personal tastes. In this study, the mass customization concept, which is one of the current production technologies, is modeled by using blockchain. In the proposed system, a blockchain-based smart contract was created to bring together the parties and establish a healthy communication. In addition, it is aimed to produce more effective products with the proposed method. By providing a simulation environment for the products to be produced, it is presented to the users' information and a feedback system is created. Thus, a consensus-based production model is being built.
Zooming Innovation in Consumer Technologies Conference (ZINC) -- MAY 26-27, 2020 -- ELECTR NETWORK
Keywords: blockchain; mass customization; smart contract